2018
DOI: 10.1002/jclp.22704
|View full text |Cite
|
Sign up to set email alerts
|

The Alliance and Rupture Observation Scale (AROS): Development and validation of an alliance and rupture measure for repeated observations within psychotherapy sessions

Abstract: Objective: The aim of this study was to test a new observerrated instrument, the Alliance and Rupture Observation Scale (AROS). It was designed for repeated measurements of the alliance within sessions and to detect alliance ruptures.Method: Videotaped therapy sessions with depressed adults were analyzed. Reliability was mainly assessed as inter-rater reliability. Convergent, predictive, and discriminant validity of the AROS was assessed by comparing the instrument with both observer-rated and patient-rated me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Therapists need to be intentional in soliciting client input, and they need to do so on an ongoing basis if they are to be prepared to minimize or address fluctuations in alliance strength and quality (Eubanks et al, 2018;Larsson et al, 2019). The importance of this is underscored by the data on how poorly therapists are able to judge when clients are at risk of treatment failure or are deteriorating (Hannan et al, 2005;Hatfield et al, 2010) or to identify what clients perceive to have been the most effective in a particular session (Bedi & Hayes, 2019).…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapists need to be intentional in soliciting client input, and they need to do so on an ongoing basis if they are to be prepared to minimize or address fluctuations in alliance strength and quality (Eubanks et al, 2018;Larsson et al, 2019). The importance of this is underscored by the data on how poorly therapists are able to judge when clients are at risk of treatment failure or are deteriorating (Hannan et al, 2005;Hatfield et al, 2010) or to identify what clients perceive to have been the most effective in a particular session (Bedi & Hayes, 2019).…”
Section: Treatmentmentioning
confidence: 99%
“…From this framework, strong alliances are characterized by collaboration or mutuality, manifest as complementarity in client-therapist interactions, which Larsson et al (2019) identified as one of the bond elements in an alliance. In fact, research has supported this link between alliance and complementarity (e.g., Friedlander, 1993;Kiesler & Watkins, 1989;Svartberg & Stiles, 1992).…”
Section: Models Concerning Client-therapist Interdependencementioning
confidence: 99%